Clinical features and prognosis of 118 children with histiocytic necrotizing lymphadenitis - Zhang, D (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To explore the clinical features and prognosis of children with histiocytic necrotizing lymphadenitis (HNL). Methods: The clinical data of 118 children with HNL diagnosed and treated in the Department of Rheumatology and Immunology of Children's Hospital, Capital Institute of Pediatrics from January 2014 to December 2021 were retrospectively analyzed. The clinical symptoms, laboratory examination, imaging examination, pathological findings, treatment and follow-up were analyzed. Results: Among the 118 patients, 69 were males and 49 were females. The age of onset was 10.0 (8.0, 12.0) years, ranging from 1.5 to 16.0 years. All the children had fever lymph node enlargement, blood system involvement in 74 cases (62.7%), skin injury in 39 cases (33.1%). The main manifestations of laboratory examination were increased erythrocyte sedimentation rate in 90 cases (76.3%), decreased hemoglobin in 58 cases (49.2%), decreased white blood cells in 54 cases (45.8%) and positive antinuclear antibody in 35 cases (29.7%). Ninety-seven cases (82.2%) underwent B-mode ultrasound of lymph nodes, showing nodular lesions with low echo in the neck; 22 cases (18.6%) underwent cervical X-ray and (or) CT; 7 cases (5.9%) underwent cervical magnetic resonance imaging. Lymph node biopsy was performed in all 118 cases, and the pathological results did not support malignant diseases such as lymphoma or Epstein-Barr virus infection, suggesting HNL. Fifty-seven cases (48.3%) recovered without treatment, 61 cases (51.7%) received oral steroid therapy, and 4 cases (3.4%) received indomethacin as anal stopper. The 118 cases were followed up for 4 (2, 6) years, ranging from 1 to 7 years, 87 cases (73.7%) had one onset and did not develop into other rheumatological diseases, and 24 cases (20.3%) had different degrees of recurrence, 7 cases (5.9%) had multiple system injuries, and all of the tested autoantibodies were positive for medium and high titers. All of them developed into other rheumatic immune diseases, among which 5 cases developed into systemic lupus erythematosus and 2 cases developed into Sjogren's syndrome; 7 cases were given oral steroid therapy, including 6 cases plus immunosuppressant and 2 cases receiving methylprednisolone 20 mg/kg shock therapy. Conclusions: The first-onset HNL portion is self-healing, hormone-sensitive and has a good prognosis. For HNL with repeated disease and multiple system injury, antinuclear antibody titer should be monitored during follow-up, and attention should be paid to the possibility of developing into other rheumatological diseases, with poor prognosis